2009
DOI: 10.1027/1618-3169.56.6.397
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Imagery and Repetition Priming

Abstract: This study examined the impact of odor naming and imagery ability on the capacity of female participants to form odor images, as indexed by a novel olfactory repetition priming task. Experiment 1 involved three conditions - olfactory and visual imagery priming, and a no-prime control. Odor imagery priming was only obtained in good odor namers. Experiment 2 used the same conditions, but altered the nature of the hit-rate trials to test how odor imagery might facilitate performance in good odor namers. Odor imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…In fact Lyman and McDaniel (1990) are the only group to report a significant correlation between imagery and task performance, but this study has been criticized, as it is unclear whether the reported imagery performance was mediated by verbal codes (see Stevenson and Case, 2005). Other studies have failed to find any link with performance, including Lyman (1988), and Tomiczek and Stevenson (2009). The latter study explored in some detail the predictors of enhanced imagery performance.…”
Section: Differences Between Processing In Olfaction and Other Modalimentioning
confidence: 92%
See 1 more Smart Citation
“…In fact Lyman and McDaniel (1990) are the only group to report a significant correlation between imagery and task performance, but this study has been criticized, as it is unclear whether the reported imagery performance was mediated by verbal codes (see Stevenson and Case, 2005). Other studies have failed to find any link with performance, including Lyman (1988), and Tomiczek and Stevenson (2009). The latter study explored in some detail the predictors of enhanced imagery performance.…”
Section: Differences Between Processing In Olfaction and Other Modalimentioning
confidence: 92%
“…The olfactory literature on these topics presents a far more complex and seemingly confusing picture. First, after decades of disagreement, it now appears that trying to imagine an odor does have several detectable consequences: (1) it activates brain regions, including primary processing areas, which are also active during real smelling (e.g., Djordjevic et al, 2005); (2) it improves various psychological capacities, such as enhancing the detection of threshold level odors (Djordjevic et al, 2004) and priming (Tomiczek and Stevenson, 2009); (3) it mimics various psychophysical parameters, relating to olfactory interactions, intensity and quality (e.g., Carrasco and Ridout, 1993); and (4) it generates olfactomotor responses (sniffing behavior) that closely approximate what is observed during actual smelling (e.g., Bensafi et al, 2003). While, a number of studies have failed to find improved psychological capacities (e.g., Crowder and Schab, 1995) or mimicking of psychological effects observed with real odors (e.g., Herz, 2000), the weight of evidence suggests that trying to imagine a smell can influence a variety of psychological, physiological and neural variables, in much the same way as actual smelling can.…”
Section: Differences Between Processing In Olfaction and Other Modalimentioning
confidence: 99%
“…The results showed that odors that were difficult to name also were difficult to imagine and that prior learning of the odor names exerted a positive effect on imagery capacity. Moreover, Tomiczek and Stevenson (2009) reported that odor imagery priming was prevalent only among good odor namers and appeared to be the result of a generic activation of olfactory neural networks when the participants tried to form an odor image. Importantly, Tomiczek and Stevenson (2009) suggested that this could occur in dependently of any consciously reported olfactory image.…”
Section: Factors Moderating Olfactory Imagery Capacitymentioning
confidence: 99%
“…However, a more recent set of experiments (Tomiczek and Stevenson, 2009) calls this into question and argues that the same perceptual state is not elicited, rather similar structures that are utilized for olfactory perception in general are activated. Tomiczek and Stevenson (2009) assert that we do not imagine a specific odor, rather there is a general overall increase in activation across areas in the olfactory system that are responsive to odorants similar to the imagined odor.…”
Section: No Olfactory Awareness Without Qualitative-consciousnessmentioning
confidence: 99%
“…Tomiczek and Stevenson (2009) assert that we do not imagine a specific odor, rather there is a general overall increase in activation across areas in the olfactory system that are responsive to odorants similar to the imagined odor. While their results indicate that the imagine state does not have the same exact content it does focus us in the right direction.…”
Section: No Olfactory Awareness Without Qualitative-consciousnessmentioning
confidence: 99%